THE EFFECTS OF REAL GDP, INFLATION, FDI, AND BUSINESS REGULATION TO DOMESTIC INVESTMENT: A CASE OF THE ASEAN 5 IN 2003-2012 - Rizky Helmi Handoyo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
ASEAN as a group of developing economies or emerging markets and strategic market becomes a place for investment that attracts many investors. ASEAN 5 namely Indonesia, Malaysia, Singapore, the Philippines and Thailand showed a unique movement in the period before the 2008 global financial crisis to post-crisis. Seeing the movement of the economic growth, it is needed to see how the investment role in supporting the growth of a country's output. Which investment is definitely an important factor needed by all countries as a driver of economic and domestic development. So it is important to find out how the other important macroeconomics variable namely real GDP, inflation, FDI, and business regulation in the period 2003 to 2012 affect domestic investment in ASEAN 5 countries. By using Panel Data Analysis, this research found that several important points regarding those objectives. Revealed that real GDP has a significant positive effect on domestic investment. While FDI and business regulation have significantly negative effects on domestic investment. But Inflation is likely not a big deal for domestic investors which it is insignificant affecting the domestic investment in ASEAN 5 for 2003-2012 case. Those findings explain that the government has to manage or even put more intensive effort towards GDP performance by implementing pro-investment policy. And also fiscal policy is one of important drivers for domestic investment. Each country has to increase the quality of human resources, infrastructure, while in the same time, good governance and efficient regulation is needed in most countries. Reduction of procedures and bureaucracy quality improvement are the most priorities in the ASEAN 5 countries. And domestic investors and government together have to put more efforts in making improvement and technological innovation. Keywords: Domestic Investment, Real GDP, Inflation, FDI, Business Regulation, ASEAN 5.